A Novel Method to Broaden the Single-Mode Bandwidth of the Rectangular Waveguide. (29th March 2022) - Xie, Tingting; Cheng, Xiaohe; Yao, Yuan; Yang, Yaohui; Zhang, Ting; Yu, Junsheng; Chen, Xiaodong
Abstract : In this paper, a new class of broadband and low-loss transmission line called slotted rectangular waveguide (SRW) is proposed and analyzed. The proposed SRW consists of the rectangular waveguide and the inverted low-loss slotline, which can selectively suppress the higher-order mode (TE20 mode) and broaden the single dominant mode (TE10 mode) bandwidth in a rectangular waveguide (RW). The design principle and transmission characteristics of the SRW are illustrated and analyzed in this work. The transmission dominant mode bandwidth of the proposed SRW is analyzed and compared with the classic rectangular waveguide (RW), in which the dominant mode bandwidth of 60–155 GHz (88.4% bandwidth) is broader than the RW bandwidth of 60–116 GHz (63%). Two feed structures that can excite the two operating bandwidths (W and D band) of them separately are also designed. The SRW and transition exhibit broadband and low-loss characteristics from 75 GHz to 155 GHz, in which the transmission loss is lower than 0.68 dB and the return loss is over 18 dB.